ANDREA'S STRUGGLE TO NEGOTIATE WITH WORKPLACE CULTURE IN LAUREN WEISBERGER'S THE DEVIL WEARS PRADA: A MARXISM PERSPECTIVE - Januarsyah Rudy Maulana, - (2010)
The study entitled "Andrea's Struggle to Negotiate with Workplace Culture in Lauren Weisberger's The Devil Wears Prada: A Marxism Perspective" aims to investigate the form of oppression of the capitalist to the working class and the struggle to negotiate the oppression. The study is qualitative in nature framed within the textual analysis approach. It employs Marxism perspective including several theories argued by Marx's and Engels's works, Bressler (1994), Eagleton (1976), Zartman (2000) etc to analyze the textual evidences from the novel Lauren Weisberger's The Devil Wears Prada. The results show that the types of oppression of the capitalist are classified into abuse, exploitation and alienation. On the other hand, there are three negotiation processes experienced by Andrea to struggle against the oppression: autonomous individual, keep the bargain on and emotion control. It is recommended further study be conducted to get a deeper understanding in analyzing the issues of negotiation.